Budidaya Jamur Kuping (Auricularia auricula [Hook] Underw.) dalam Tegakan Hutan pada Substrat Log Kayu Afrika (Maesopsis eminii Engl.) - IGK Tapa Darma (Institut Pertanian Bogor (IPB University), 2000)
Ear mushroom (Auricularia auricula (Hook) Underw.) were produced by cultivating the fungus on logs of kayu afrika (Maesopsis eminii Engl.). The logs of 60 cm long having a diameters of 19-25 cm were first solar dried for two months and subsequently soaked in water for three days. Thereafter, they were inoculated with the fungus by placing the inocula in the 3-4 cm deep holes made by boring the superficial part of the logs and then the inoculated logs were incubated in the room by wrapping with black polyethylene sheet for 18 days. The experiment of the cultivation was carried out with the treatment of the incubated logs as follows: i) logs placed on the forest floor and covered with black polyethylene sheets (0.3 mm thick), ii) logs were placed on the forest floor and covered with sisal sacs, iii) logs were hanged on the tree stem and covered with black polyethylene sheets, and iv) logs were hanged on the tree stem and covered with sisal sacs. Similar conditionings and treatments were also given to fresh logs (without solar drying). The experiment was also designed to find out whether cultivating the logs under laboratory conditions affect the growth and the formation as well as the development of the fruiting bodies of the fungus. Fruiting bodies were formed on dried logs 24 days after inoculation or 6 days after cultivation, whereas none was formed on fresh logs placed in the forest stand, also, fruiting bodies was not formed on all logs placed in the laboratory. There after, every 6 days, harvesting of the mushrooms could be carried out for as long as one month (5 times harvestings). The largest mushroom production proved to be on logs hanged on the tree stem and covered with the sisal sacs.